Endovascular stent thrombectomy: the new standard of care for large vessel ischaemic stroke. Issue 8 (August 2015) - Campbell, Bruce C V; Donnan, Geoffrey A; Lees, Kennedy R; Hacke, Werner; Khatri, Pooja; Hill, Michael D; Goyal, Mayank; Mitchell, Peter J; Saver, Jeffrey L; Diener, Hans-Christoph; Davis, Stephen M
Summary: Background: Results of initial randomised trials of endovascular treatment for ischaemic stroke, published in 2013, were neutral but limited by the selection criteria used, early-generation devices with modest efficacy, non-consecutive enrolment, and treatment delays. Recent developments: In the past year, six positive trials of endovascular thrombectomy for ischaemic stroke have provided level 1 evidence for improved patient outcome compared with standard care. In most patients, thrombectomy was performed in addition to thrombolysis with intravenous alteplase, but benefits were also reported in patients ineligible for alteplase treatment. Despite differences in the details of eligibility requirements, all these trials required proof of major vessel occlusion on non-invasive imaging and most used some imaging technique to exclude patients with a large area of irreversibly injured brain tissue. The results indicate that modern thrombectomy devices achieve faster and more complete reperfusion than do older devices, leading to improved clinical outcomes compared with intravenous alteplase alone. The number needed to treat to achieve one additional patient with independent functional outcome was in the range of 3·2–7·1 and, in most patients, was in addition to the substantial efficacy of intravenous alteplase. No major safety concerns were noted, with low rates of procedural complications and no increase in symptomatic intracerebral haemorrhage. Where next?: Thrombectomy benefits patients across a range of ages and levels of clinical severity. A planned meta-analysis of individual patient data might clarify effects in under-represented subgroups, such as those with mild initial stroke severity or elderly patients. Imaging-based selection, used in some of the recent trials to exclude patients with large areas of irreversible brain injury, probably contributed to the proportion of patients with favourable outcomes. The challenge is how best to implement imaging in clinical practice to maximise benefit for the entire population and to avoid exclusion of patients with smaller yet clinically important potential to benefit. Although favourable imaging identifies patients who might benefit despite long delays from symptom onset to treatment, the proportion of patients with favourable imaging decreases with time. Health systems therefore need to be reorganised to deliver treatment as quickly as possible to maximise benefits. On the basis of available trial data, intravenous alteplase remains the initial treatment for all eligible patients within 4·5 h of stroke symptom onset. Those patients with major vessel occlusion should, in parallel, proceed to endovascular thrombectomy immediately rather than waiting for an assessment of response to alteplase, because minimising time to reperfusion is the ultimate aim of treatment.